Organoleptic Quality of Dried Candies Made from Bamboo Shoots - I Komang Adi Prinatha; I Made Purwa Dana Atmaja (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
Dried sweets are processed products made by using a rolling technique then dried under the sun or using a drying oven, in this study using bamboo shoots as processed dry sweets. This study aims to determine and describe the quality of dried sweets made from bamboo shoots in terms of organoleptic in terms of taste, aroma, texture and color. The type of research used is descriptive qualitative to determine the quality of dried sweets made from bamboo shoots, using data collection techniques: experiments, documentation, organoleptic tests, questionnaires, and Likert scales to get the best results from dried sweets made from bamboo shoots. the overall results of dried sweets made from bamboo shoots got an average rating of 90.75% so, the results of the dry sweets experiment using bamboo shoots as raw materials were successful.